The hidden sentinel of the skin: An overview on the role of interleukin-13 in atopic dermatitis - Napolitano, Maddalena; di Vico, Francesca; Ruggiero, Angelo; Fabbrocini, Gabriella; Patruno, Cataldo (Frontiers in Medicine, 2023)
Recent evidence suggests that interleukin (IL)-13 is a crucial cytokine involved in the pathogenesis of atopic dermatitis (AD). It is a central driver of type-2 T-helper inflammation and is overexpressed in lesional skin of AD patients. Upon release in peripheral skin, IL-13 activates its receptors, recruits inflammatory cells, and modifies the skin microbiome. IL-13 also reduces the expression of epidermal barrier proteins and activates sensory nerve mediating the itch transmission signal. Novel therapeutics that target IL-13 seem to be efficacious and safe for the treatment of patients with moderate-to-severe AD. The aim of our manuscript is to review the role that IL-13 plays in AD immunopathogenesis.